Education of children with disabilities during the COVID-19 pandemic in a rural school – in the experience of a school pedagogue - Śliwowski, Tomasz (Disability and education, 2023)
The article describes issues related to remote education of students with disabilities during the COVID-19 pandemic. It concerns the selection of appropriate forms of education in the case of children in a primary school in the countryside in the Białystok district in the Podlaskie Voivode-ship. It describes selected methods and forms of distance learning on the basis of changing pro-visions of the education law in the years 2019–2022. The analysis of individual cases of children with disabilities attending one school in a rural commune shows the multiplicity of possibilities of choosing methods and forms despite the pandemic. Points to the need to analyse the possibilities and difficulties of individual children learning in an institution in preparing an effective form of education for these children. The article describes the education of children with disabilities based on the experience of a school pedagogue.